PREPARATION OF THE INTERNATIONAL CONFERENCE: “MODERN ASPECTS OF SPECIAL EDUCATION AND REHABILITATION OF PERSONS WITH DISABILITIES” (Journal of Special Education and Rehabilitation, 2013)
This year, the Institute of Special Education and Rehabilitation, Faculty of Philosophy in Skopje, celebrates the anniversary “20 years from the beginning of special education and rehabilitation studies”. On that occasion, the Institute is organizing a conference with the main topic “Modern aspects of special education and rehabilitation of persons with disabilities”. The Conference has an international character and it is fourth of this kind. The International conference will take place in the hotel “Metropol” in Ohrid, during the period from 17th -19th  October. A book of abstracts and a book of papers, and the book of the presented papers will be published after the Conference. The papers are divided into 4 categories.